1986
DOI: 10.1007/bf01331511
|View full text |Cite
|
Sign up to set email alerts
|

The rheological characterization of HPG gels: Measurement of slip velocities in capillary tubes

Abstract: Measurements are reported for the properties of two hydroxypropyl guar (HPG) gels. The flow curves are composed of three distinct regions: a yield value at low stress levels, a quasi-linear region at intermediate stress or deformation rate levels, and a broad region at high deformation rate levels in which the flow is entirely dominated by slip phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 23 publications
4
20
0
2
Order By: Relevance
“…The true shear rate can be corrected by subtracting 4u s /R from the apparent shear rate. Such a correction is also known as the Mooney correction (86,87), which can produce the corrected shear rate especially at high shear rate. The dependence of wall slip on the shear stress can give additional information on extrusion instability (88,89).…”
Section: Rotational Rheometermentioning
confidence: 98%
“…The true shear rate can be corrected by subtracting 4u s /R from the apparent shear rate. Such a correction is also known as the Mooney correction (86,87), which can produce the corrected shear rate especially at high shear rate. The dependence of wall slip on the shear stress can give additional information on extrusion instability (88,89).…”
Section: Rotational Rheometermentioning
confidence: 98%
“…4a, which is much larger than the apparent viscosity measured by the rheometer. It is noted that wall slip has been characterized using the capillary viscometer for borate crosslinked hydroxypropyl guar gels (Jiang et al 1986;Kesavan et al 1993). For zirconium crosslinked CMHPG, the velocity profile again shows wall slip and negligible flow in the bulk, indicating the shear stress is still below the yield stress of the sample.…”
Section: Figure 5-comparison Of First Normal Stress Difference For 0mentioning
confidence: 98%
“…Jiang et al 5 also observed, with hydroxypropyl guar gels, that wall slip occurred more readily in tubes with smooth surfaces. The wall slip of gels was observed more readily in acrylic tubes, as compared to stainless steel tubes.…”
Section: Introductionmentioning
confidence: 94%